FINANCIAL RISK ANALYSIS IN THE BUILDING SECTOR:A CASE STUDY OF ROMANIA (GALATI COUNTY) - Barbuta, Nicoleta (Ekonomika, 2010)
The importance given to the problem of capital structure comes from the influence of debt on equity profitability (financial leverage) and the financial risk induced by debt. This paper is actually an analysis of the evolution of financial risk in the building sector during 2001–2008 on a sample of 11 enterprises in the Galati County, Romania. In this approach, we used information from the balance sheets of enterprises, provided by the Register of Commerce. To carry out this analysis two methods were used, which rely on the breakeven point and the leverage.Analysis of aggregate data reveal a low fluctuating trend of financial risk, which shows that by the end of 2008 the effects of the economic and financial crisis still have not been felt as much as statistics show in 2009. The conclusion that emerges from this study is that the world crisis produces major effects on the building sector, but they can be seen a bit later. The effects are disastrous for economy (lack of work, offs of staff, etc.), which is why the government began to seek solutions to relaunch this sector.p>